Development Strategy of WingkoBabat Industry with Good Manufacturing Practices (GMP) Method - Mohammad Yaskun; Akhlis Priya Pambudy; Khoirul Hidayat (Jurnal Mantik, 2020)
Wingko is a typical food that comes from Babat, Lamongan. To maintain product quality and safety, SME WingkoBabat needs to implement Good Manufacturing Practices (GMP). The research method used is Good Manufacturing Practices (GMP) method. GMP is carried out in 3 stages namely, Assessment of 14 aspects and 37 sub aspects of GMP, Determination of GMP levels, and Corrective Actions. Based on the assessment of aspects and sub-aspects of GMP, there were 9 deviations, namely 1 major deviation, 5 serious deviations, and 3 critical deviations. With 9 such deviations, SME WingkoBabat is included in level 4. Corrective action is carried out on deviations that occur by taking into account the types of irregularities, responsibility, audit frequency, and the deadline for repairs. So that with an increase in product quality, WingkoBabat will be able to compete with modern food and increase product sales